2008
DOI: 10.1111/j.1467-8489.2008.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosecurity in agriculture: an economic analysis of coexistence of professional and hobby production*

Abstract: One component of biosecurity is protection against invasive alien species, which are one of the most important threats worldwide to native biodiversity and economic profitability in various sectors, including agriculture. However, agricultural producers are not homogeneous. They may have different objectives and priorities, use different technologies, and occupy heterogeneous parcels of land. If the producers differ in terms of their attitude towards invasive pests and the damages they cause, there are probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…farmers not being able to alter the condition of poor boundary fences which are their neighbours’ responsibility). This was stated by several farmers during the course of the interviews, and has been demonstrated previously [47]. …”
Section: Discussionsupporting
confidence: 76%
“…farmers not being able to alter the condition of poor boundary fences which are their neighbours’ responsibility). This was stated by several farmers during the course of the interviews, and has been demonstrated previously [47]. …”
Section: Discussionsupporting
confidence: 76%
“…In examining invasions of the Colorado potato beetle in Finland between 1998 and 2002, Ceddia et al (2008) observed distinctions between utility-seeking hobby producers and profit-seeking commercial producers. They concluded that underinvestment in disease management activities is more pronounced among nonprofessional producers (Ceddia et al, 2008(Ceddia et al, , 2009. Their research supports a conclusion that professional producers have more information and use better techniques for detecting outbreaks.…”
Section: Timely Disease-eradication Practicesmentioning
confidence: 97%
“…In the United States, the agriculture and food infrastructure has such great importance globally that in 2003 it was listed as a critical infrastructure to be protected under Homeland Security Presidential Directive 7 (Horn & Breeze, 2006;Ceddia, Heikkila, & Peltola, 2008). The Marsh Report first defined infrastructures in 1997 as a "network of independent, mostly privately owned, manmade systems that function collaboratively and synergistically to produce and distribute a continuous flow of essential goods and services" (Lewis, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Protection of the agriculture and food infrastructure is the responsibility of all stakeholders in the food supply chain. Though the chain is composed of many stakeholders, livestock producers emerge as the first line of defense against animal health hazards, such as disease epidemics that threaten food supply security and animal production (Ceddia, Heikkila, & Peltola, 2008;Dement, 2008 owner (Ceddia et al, 2008;Lindell & Perry, 2004). By identifying preferred sources, perceived credibility in these sources, and preferred formats of animal health information, risk communicators can help reduce agricultural vulnerability by more effectively reaching livestock producers with critical hazard information.…”
Section: Introduction/need For the Studymentioning
confidence: 99%